Modelling Motorcycle Ownership In Malaysia. - Leong, Lee Vien; Mohd. Sadullah, Ahmad Farhan (2005)
High composition of motorcycles in a mixed traffic situation is common in most Asian countries. In Malaysia, there are approximately 5.8 million motorcycles on the roads and on the same note, accidents rate involving motorcycles are almost half of the total road fatalities recorded.